STATE BUDGET ANALYSIS AND TO ACHIEVE LOW GOVERMENT DEBT WITH SOME INSTRUMENTS: ISLAMIC FINANCE AND PUBLIC-PRIVATE PARTNERSHIPS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article analyze situation of govermental debt in Uzbekistan and some countries. In the article are given some solutions to this problem such as Islamic fianancing instruments and public-private partnerships